The Jewish Critique of Christianity: In Search of a New Narrative - Lasker, Daniel J. (Studies in Christian-Jewish Relations, 2011)
The old narrative of the Jewish critique of Christianity was simple: Jews criticized Christianity as a reaction to the Christian mission to the Jews; if Christians had not attempted to convince Jews to convert to Christianity, there would have been no reason for Jews to say anything negative about the majority religion. Judaism is a religion of tolerance, at least towards members of other religions, and, therefore, it was not a Jewish concern how Gentiles worshipped. But as medieval Christians tried more and more to convince Jews to convert, Jewish thinkers answered this challenge by developing arguments to be used against Christian doctrines. In light of recent research, this narrative, as comfortable as it might be to Jews, is no longer tenable. Jews criticized Christianity even in the absence of a Christian missionary threat, such as in Muslim countries. Furthermore, not all Christian anti-Jewish polemic should be understood as part of a conversionary campaign. Thus, there is a need for a new narrative to explain the proliferation of Jewish critiques of Christianity. This article discusses the various considerations at play in the search for that new narrative.